Enclave - Aguirre, Ann (Feiwel and Friends, 2011)
In a post-apocalyptic future, fifteen-year-old Deuce, a loyal Huntress, brings back meat while avoiding the Freaks outside her enclave, but when she is partnered with the mysterious outsider, Fade, she begins to see that the strict ways of the elders may be wrong-- and dangerous.